Utility of the modified frailty index in predicting toxicity and cancer outcomes for older adults with advanced pancreatic cancer receiving first-line palliative chemotherapy. Issue 1 (January 2021) - Rittberg, Rebekah; Zhang, Hanbo; Lambert, Pascal; Kudlovich, Robert; Kim, Christina A.; Dawe, David E.
ABSTRACT: Background: Pancreatic cancer primarily affects older adults and is associated with a high morbidity and mortality. Identifying frail patients with advanced pancreatic cancer (APC) helps to mitigate the risks of chemotherapy (CT). The modified Frailty Index (mFI) is an 11-point deficit measure used to identify frail patients. Although validated in surgical fields, it has not been assessed in an APC population. Methods: A retrospective cohort study evaluated consecutive patients, aged ≥65 years, diagnosed with APC from 2011 to 2016 and treated with first line palliative-intent CT. mFI was categorized as: 0, 1, 2 and ≥ 3. Descriptive analysis was completed comparing patient characteristics, CT toxicity, response to treatment, and overall survival (OS) by mFI score. Results: 87 patients with APC received palliative CT. Median age was 71 (65–88), 54% male. A mFI score of 0, 1, 2, and ≥ 3 occurred for 20 (23%), 28 (32.2%), 25 (28.7%) and 14 (16.1%) patients respectively. Patients with mFI scores of 0–1 were more likely to receive: 5-fluorouracil, irinotecan and oxaliplatin. CT toxicity, emergency room (ED) and urgent cancer clinic (UCC) presentation, and hospitalization length did not differ by mFI. Longer OS was associated with better ECOG and receipt of combination CT. Conclusion: This is the first assessment of the mFI in an APC population receiving CT. The mFI score did not correlate with toxicity, ED/UCC visits, hospitalization length or OS. Ongoing assessment of tools that accurately identify frailty in patients with APC is critical to help better select candidates for aggressive CT. Highlights: mFI is a deficit measure validated in surgical fields to identify frailty. This is the first assessment of mFI in APC or patients receiving chemotherapy. mFI did not correlate with chemotherapy toxicity, admission length or survival. Multidrug chemotherapy and better performance status correlate with better survival.